Answer:
a) eight and seven ninths minus three and four sixths
Step-by-step explanation:
The required result is ![5\frac{6}{54}](https://tex.z-dn.net/?f=5%5Cfrac%7B6%7D%7B54%7D)
a)
![8\frac{7}{9} -3\frac{4}{6}\\\\=\frac{79}{9} -\frac{22}{6} \\\\Simplifying\ the\ expression:\\\\=\frac{474-198}{54} \\\\=\frac{276}{54}\\\\=5\frac{6}{54}](https://tex.z-dn.net/?f=8%5Cfrac%7B7%7D%7B9%7D%20-3%5Cfrac%7B4%7D%7B6%7D%5C%5C%5C%5C%3D%5Cfrac%7B79%7D%7B9%7D%20%20-%5Cfrac%7B22%7D%7B6%7D%20%5C%5C%5C%5CSimplifying%5C%20the%5C%20expression%3A%5C%5C%5C%5C%3D%5Cfrac%7B474-198%7D%7B54%7D%20%5C%5C%5C%5C%3D%5Cfrac%7B276%7D%7B54%7D%5C%5C%5C%5C%3D5%5Cfrac%7B6%7D%7B54%7D)
b)
![6\frac{8}{9} -1\frac{5}{6}\\\\=\frac{62}{9} -\frac{11}{6} \\\\Simplifying\ the\ expression:\\\\=\frac{372-99}{54} \\\\=\frac{273}{54}\\\\=5\frac{3}{54}](https://tex.z-dn.net/?f=6%5Cfrac%7B8%7D%7B9%7D%20-1%5Cfrac%7B5%7D%7B6%7D%5C%5C%5C%5C%3D%5Cfrac%7B62%7D%7B9%7D%20%20-%5Cfrac%7B11%7D%7B6%7D%20%5C%5C%5C%5CSimplifying%5C%20the%5C%20expression%3A%5C%5C%5C%5C%3D%5Cfrac%7B372-99%7D%7B54%7D%20%5C%5C%5C%5C%3D%5Cfrac%7B273%7D%7B54%7D%5C%5C%5C%5C%3D5%5Cfrac%7B3%7D%7B54%7D)
c)
![4\frac{1}{6} +1\frac{1}{9}\\\\=\frac{10}{9} +\frac{25}{6} \\\\Simplifying\ the\ expression:\\\\=\frac{60+225}{54} \\\\=\frac{285}{54}\\\\=5\frac{15 }{54}](https://tex.z-dn.net/?f=4%5Cfrac%7B1%7D%7B6%7D%20%2B1%5Cfrac%7B1%7D%7B9%7D%5C%5C%5C%5C%3D%5Cfrac%7B10%7D%7B9%7D%20%20%2B%5Cfrac%7B25%7D%7B6%7D%20%5C%5C%5C%5CSimplifying%5C%20the%5C%20expression%3A%5C%5C%5C%5C%3D%5Cfrac%7B60%2B225%7D%7B54%7D%20%5C%5C%5C%5C%3D%5Cfrac%7B285%7D%7B54%7D%5C%5C%5C%5C%3D5%5Cfrac%7B15%20%7D%7B54%7D)
d)
![3\frac{3}{6} +2\frac{4}{9}\\\\=\frac{22}{9} +\frac{21}{6} \\\\Simplifying\ the\ expression:\\\\=\frac{132+189}{54} \\\\=\frac{321}{54}\\\\=5\frac{51 }{54}](https://tex.z-dn.net/?f=3%5Cfrac%7B3%7D%7B6%7D%20%2B2%5Cfrac%7B4%7D%7B9%7D%5C%5C%5C%5C%3D%5Cfrac%7B22%7D%7B9%7D%20%20%2B%5Cfrac%7B21%7D%7B6%7D%20%5C%5C%5C%5CSimplifying%5C%20the%5C%20expression%3A%5C%5C%5C%5C%3D%5Cfrac%7B132%2B189%7D%7B54%7D%20%5C%5C%5C%5C%3D%5Cfrac%7B321%7D%7B54%7D%5C%5C%5C%5C%3D5%5Cfrac%7B51%20%7D%7B54%7D)
Answer:
7y+4
Step-by-step explanation:
combine liked terms
The equation which represents the given graph g(x) is 2ˣ-1.
<h3>
What is Equation?</h3>
Equations are mathematical statements containing two algebraic expressions on both sides of an 'equal to (=)' sign.
Here, given graph passes through origin.
Put x = 0 in all the given equation and verify which equations gives result as zero.
Put x = 0 in option A
g(0) = 2⁰⁺¹ = 2 ≠ 0
in option B
g(0) = 2⁰-1 = 1 - 1 = 0
Thus, option B g(x) = 2ˣ-1 is the correct expression for the given graph.
Learn more about Equations from:
brainly.com/question/10413253
#SPJ1
Answer:
![x \geq 11](https://tex.z-dn.net/?f=x%20%5Cgeq%2011)
Step-by-step explanation:
![x+7 \geq 18](https://tex.z-dn.net/?f=x%2B7%20%5Cgeq%2018)
![x \geq 18-7](https://tex.z-dn.net/?f=x%20%5Cgeq%2018-7)
![x \geq 11](https://tex.z-dn.net/?f=x%20%5Cgeq%2011)
The variable is X .........